Effect of Schinus areira L. essential oil on attraction, reproductive behavior, and survival of Ceratitis capitata Wiedemann - Jofré Barud, Flavia; Gomez, María Pía; Ruiz, María Josefina; Bachmann, Guillermo Enrique; Segura, Diego Fernando; Vera, María Teresa; Lopez, María Liza (MDPI, 2025)
The essential oil (EO) of Schinus areira exhibits a chemical composition dominated by monoterpene and sesquiterpene hydrocarbons, with α-phellandrene, limonene, α-pinene, and p-cymene as major constituents. This study aimed to evaluate the effects of S. areira EO on the biology and behavior of the Mediterranean fruit fly, Ceratitis capitata, particularly its attraction to the EO and the impact on its reproductive behavior and survival. Females were attracted at the initial choice and the time spent in the arm of the Y-tube olfactometer with the EO was longer, while males were attracted at the final choice, indicating the attractive potential of S. areira EO for both sexes of C. capitata. Within the context of the sterile insect technique (SIT), the better performance of released sterile males allows more copulations with wild females in competition with wild males, increasing the efficacy of the SIT. Exposure of tsl sterile males to the EO did not enhance their sexual competitiveness and increased latency to initiate copulation, indicating potential adverse effects. In addition, in oviposition assays, only a low concentration of the EO stimulated egg-laying on treated substrates, possibly due to the absence of deterrent compounds such as linalool. Finally, the LD50 of the EO was <25 µg/fly for both females and males, at 72 h post-treatment. These findings highlight the potential of EOs as biopesticides that influence the behaviors of C. capitata and emphasize the need for further studies to optimize their application in integrated pest management strategies, including the SIT.